Vaccine adjuvants for immunotherapy: type, mechanisms and clinical applications - Desai, Nimeet; Gotru, Sherrin; Salave, Sagar; Vora, Lalitkumar K. (Frontiers in Biomaterials Science, 2025)
Immunotherapy has emerged as a powerful approach in treating various diseases, yet its success often hinges on the efficacy of adjuvants, agents that boost immune responses to therapeutic targets. Traditional adjuvants have offered foundational support but may fall short in achieving the specificity and potency required for advanced therapies. This review highlights a new generation of adjuvants poised to address these limitations. We explore a range of innovative agents, including non-inflammatory nucleic acid adjuvants, bacterial derivatives, and synthetic molecules, which are redefining the role of adjuvants in immunotherapy. These emerging agents hold promise for enhancing immune responses while tailoring therapies to specific disease contexts, from cancer to infectious diseases. By examining the applications and potential of these adjuvants, this review aims to provide a comprehensive understanding of how they can advance immunotherapy to new levels of efficacy and precision. Through the development of these novel adjuvants, immunotherapy stands to achieve more targeted and sustained impacts, paving the way for improved outcomes in patient care.